HUBUNGAN DUKUNGAN KELUARGA TERHADAP KEPATUHAN DIET HIPERTENSI PADA PENDERITA HIPERTENSI DI KELURAHAN TAPOS DEPOK - Amelia, Rosa; Kurniawati, Indah (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
The prevalence of hypertension will continue to increase globally and it is predicted that by 2025 there will be a high increase of around 1.15 billion cases of hypertension worldwide. Hypertension that does not get good treatment will cause complications and death. Patient with hypertension need family support is needed for a hypertensive diet. This study aims to determine the relationship of family support for adherence to the hypertension diet in hypertensive patients in Tapos Depok Village. This research method uses a cross-sectional research design. This research was conducted in Tapos Depok Village with a total sample of 93 respondents. Sampling in this study using cluster sampling method and Simple Random Sampling technique. Data analysis using the Chi-Square test. The results obtained values ??p=0.001, which means there is a relationship between family support for compliance with hypertension diet in hypertensive patients in Tapos Depok Village. Obtained values OR=5,704 which means respondents who received good family support will more easily comply with their hypertension diet, compared with respondents who did not family support.